Petrography and provenance of basement clasts and clast variability in CRP-3 drillcore (Victoria Land Basin, Antarctica) - SANDRONI, S.; TALARICO, F. (2001)
Distribution patterns and petrographical and mineral chemistry data are described for the most representative basement lithologies occurring as clasts in the c. 824 m thick Tertiary sedimentary sequence at the CRP-3 drillsite. These are granule to boulder grain size clasts of igneous and metamorphic rocks. Within the basement clast assemblage, granitoid pebbles are the predominant lithology. They consist of dominant grey biotite-bearing monzogranite, pink biotite-hornblende monzogranite, and biotite-bearing leucomonzogranite. Minor lithologies include: actinolite-bearing leucotonalite, microgranite, biotite-hornblende quartz-monzonitic porphryry, and foliated biotite leucomonzogranite. Metamorphic clasts include rocks of both granitic and sedimentary derivation. They include mylonitic biotite orthogneiss, with or without garnet, muscovite-bearing quartzite, sillimanite-biotite paragneiss, biotite meta-sandstone, biotite spotted schist, biotite-calcite-clinoamphibole meta-feldspathic arenite, biotite-calcite-clinozoisite meta-siltstone, biotite±clinoamphibole meta-marl, and graphite-bearing marble. As in previous CRP drillcores, the ubiquitous occurrence of biotite±hornblende monzogranite pebbles is indicative of a local provenance, closely mirroring the dominance of these lithologies in the on-shore basement, where the Cambro-Ordovician Granite Harbour Intrusive Complex forms the most extensively exposed rock unit.